PENGELOLAAN WISATA ALAM CURUG GLAWE DAN BUKIT SELO ARJUNO DI KABUPATEN KENDAL JAWA TENGAH BERBASIS ECOTOURISM - A, Isfajar; Kuswardono, Singgih; Miftahudin, Ahmad; Sunahrowi, Sunahrowi (Indonesian Journal of Conservation, 2017)
Semarang State University as a conservation university in Indonesia is required to have a role in the environment around the campus and also in the wider environment that is throughout Indonesia. Academicians Semarang State University where in it is the teacher (lecturer), education personnel, and others should be hand in hand to realize the ideals of the luhur. Each individual can play a role in this conservation field in accordance with its capacity and capability. With this simultaneous and simultaneous movement, it is expected that Semarang State University really becomes a superior university in playing its role in society, nation and state. The target in this service is the manager of Curug Glawe natural tourism in Cening and Bukit Selo Arjuno village in Kedungboto Village using approach developed through ecotourism concept. The method to be applied in this training is the SWOT method. The selection of targeted methods and objects is based on facts resulting from initial observation that this nature tourism has good strength and attractiveness and prospective (strength), weakness in the management and supervision (weaknesses), the opportunity to be developed and conceptualized well (opportunities ) and there are some serious threats to sustainability (threats). Based on the facts, the ecotourism training activities in the management of nature tourism Curug Glawe and the management of nature tourism of Selo Arjuno hill by the devotees need a proper method to find the solution faced by the object of devotion, that is by applying the SWOT method (strength, weaknesses , opportunities, and threats). Selection of this method is also based on the needs and objectives for the conservation values as the basis of ecotourism can be realized.